Firefly wedding. 1 - Tachibana, Oreco (Viz Media, 2025)
Afflicted with a heart condition, Meiji-era noblewoman Satoko is determined to secure a marriage that will benefit her family before she dies. But before she can realize her goal, she's targeted by a mysterious assassin named Shinpei. In a last-ditch effort to save her life, Satoko asks her would-be murderer to marry her. Her proposal isn't sincere, but unfortunately for her, Shinpei loves as intensely as he kills. Can Satoko find a way to break the engagement without losing her life? On the surface, Satoko has it all--she's beautiful, the daughter of a nobleman, and at a prime age for marriage. Unfortunately, she is also quite ill and only has a short time left to live. Before she can secure a marriage that will redeem her worth in her family's eyes, she finds herself the target of the mysterious assassin Shinpei, and her plans are put in jeopardy. In order to save herself, she makes a desperate proposal--of marriage! When it comes to love, however, Shinpei takes "until death do we part" seriously.--